2014
DOI: 10.1089/zeb.2013.0947
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Protects Against Anxiogenic-Like Effect Induced by Methylmercury in Zebrafish: Action on the Serotonergic System

Abstract: To evaluate the protector effect of ascorbic acid (AA) against anxiogenic-like effect induced by methylmercury (MeHg) exposure, adult zebrafish were treated with AA (2 mg g(-1), intraperitoneal [i.p.]) before MeHg administration (1.0 μg g(-1), i.p.). Groups were tested for the light/dark preference as a behavioral model of anxiety, and the content of serotonin and its oxidized metabolite tryptamine-4,5-dione (T-4,5-D) in the brain was determined by high-performance liquid chromatography. MeHg has produced a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The authors suggested that the alleviating effect of Vit C on stress-related rearing behavior was exerted via modulation of corticosterone, whereas the effect on freezing behavior via modulation of corticotropin-releasing hormone or adrenocorticotropin-releasing hormone [ 186 ]. Puty et al [ 187 ] in turn suggested that Vit C plays anxiolytic-like effect via affecting serotonergic system. The researchers evaluated the protective effect of Vit C against methylmercury (MeHg)-induced anxiogenic-like effect in zebrafish.…”
Section: Role Of Vitamin C In Psychiatric Disordersmentioning
confidence: 99%
“…The authors suggested that the alleviating effect of Vit C on stress-related rearing behavior was exerted via modulation of corticosterone, whereas the effect on freezing behavior via modulation of corticotropin-releasing hormone or adrenocorticotropin-releasing hormone [ 186 ]. Puty et al [ 187 ] in turn suggested that Vit C plays anxiolytic-like effect via affecting serotonergic system. The researchers evaluated the protective effect of Vit C against methylmercury (MeHg)-induced anxiogenic-like effect in zebrafish.…”
Section: Role Of Vitamin C In Psychiatric Disordersmentioning
confidence: 99%
“…Different compounds have already been shown to alter this innate behavior in zebrafish. Exposure to 0.5 % ethanol, for example, has an anxiolytic effect in such light–dark preference assays (Sackerman et al, ), whereas treatment with methylmercury has an anxiogenic effect (Puty et al, ).…”
Section: Amygdala‐relevant Behavioral Assays In Zebrafishmentioning
confidence: 99%
“…In addition to the compounds discussed above (agomelatine, NAC, and omega-3 fatty acids), we also found some evidence of anxiolytic effects in clinical trials and animal studies for ascorbic acid (vitamin C) and the mGlu 2/3 receptor agonist LY354740. Although ascorbic acid has presented anxiolytic effects in different animal models in rats,146 mice,147 and zebrafish,148 evidence of its anxiolytic effects in humans is limited. Only one small randomized double-blind placeb-controlled clinical trial (n=42) with ascorbic acid conducted with normal volunteers was found: its results were that ascorbic acid decreased anxiety levels 149.…”
Section: Resultsmentioning
confidence: 99%